Adaptation Capability and Competitiveness for micro-grocery store, Cuitzeo, Mexico - Valenzo-Jiménez, Marco Alberto; Gonzaléz-Samaniego, Arcadio (Mercados y Negocios, 2021)
The aim of the research is to determine if the adaptation capability is a factor of competitiveness in micro micro-grocery store, Cuitzeo, Mexico. The metyod used consisted of applying a survey to a sample of 350 mexican companies. The results indicate that adaptation capability is a factor of competitiveness in a regular range. It is concluded that the companies studied must increase the use of new technologies and the planning of the company to improve their competitiveness.